Clinical and Pathological Features of Chinese Patients with Type 2 Diabetes, Biopsy-Proven Diabetic Kidney Disease, and Rapid eGFR Decline - Qin C; Wang Y; Zhao L; Zhang J; Ren H; Zou Y; Wu Y; Wang T; Zhao Y; Zhang R; Xu H; Zhang J; et al. (Diabetes, Metabolic Syndrome and Obesity, 2022)
Chunmei Qin,1– 3 Yiting Wang,1,2 Lijun Zhao,1,2 Junlin Zhang,1,2 Honghong Ren,1,2 Yutong Zou,1,2 Yucheng Wu,1,2 Tingli Wang,1,2 Yuancheng Zhao,1,2 Rui Zhang,1,2 Huan Xu,4 Jie Zhang,5 Mark E Cooper,6 Fang Liu1,2 1Division of Nephrology, West China Hospital of Sichuan University, Chengdu, People’s Republic of China; 2Laboratory of Diabetic Kidney Disease, Centre of Diabetes and Metabolism Research, West China Hospital of Sichuan University, Chengdu, People’s Republic of China; 3Department of Nephrology, Luzhou People’s Hospital, Luzhou, People’s Republic of China; 4Division of Pathology, West China Hospital of Sichuan University, Chengdu, People’s Republic of China; 5Key Laboratory of Transplant Engineering and Immunology, Chengdu, People’s Republic of China; 6Department of Diabetes, Central Clinical School, Monash University, Melbourne, AustraliaCorrespondence: Fang Liu, Division of Nephrology, West China Hospital of Sichuan University, No. 37, Guoxue Alley, Chengdu, Sichuan, 610041, People’s Republic of China, Tel +86-28-18980601214, Fax +86-28-85422335, Email liufangfh@163.comObjective: The rate of kidney function decline in patients with diabetic kidney disease (DKD) is known to differ. This study analyzed the clinicopathologic features and related risk factors affecting long-term renal survival in Chinese type 2 diabetic patients with rapid estimated glomerular filtration rate (eGFR) decline.Methods: In this retrospective descriptive study, 191 DKD patients were first classified as rapid eGFR decliners and slow eGFR decliners on the basis of the median eGFR slope value (− 8.0 mL/min/1.73 m2/year). In total, 96 patients with rapid eGFR decline were included in the analyses and subsequently allocated to end-stage renal disease (ESRD) and non-ESRD groups. Baseline clinicopathological data of rapid eGFR decliners were collected. Cox proportional hazard analysis was performed to calculate the hazard ratios (HRs) for progression to ESRD.Results: During a median follow-up of 25 months, 52 (54.2%) rapid eGFR decliners progressed to ESRD. These 52 rapid eGFR decliners had poorer renal function, lower hemoglobin and albumin concentrations, higher total cholesterol and baseline proteinuria levels, and more severe interstitial inflammation than those who did not progress to ESRD. After adjustment for age, gender, baseline eGFR, proteinuria, hemoglobin level, serum albumin concentration, and histopathologic parameters, multivariate Cox proportional hazard analysis revealed that eGFR (HR 0.973, 95% CI 0.956– 0.989) and proteinuria (HR 1.125, 95% CI 1.030– 1.228) were associated with the increased risk of progression to ESRD.Conclusion: Higher proteinuria and lower eGFR were independent risk factors for renal progression in Chinese patients with type 2 diabetes and rapid eGFR decline.Keywords: diabetic kidney disease, rapid eGFR decline, clinical, pathological, type 2 diabetes